POSITIONS OF THE VISEGRAD FOUR COUTRIES AND THE BALTIC STATES ON THE RUSSIAN-UKRAINIAN CONFLICT - Tetiana Sydoruk; Dmytro Tyshchenko (Torun International Studies, 2016)
The article analyses the positions of the Visegrad Group and the Baltic countries on the Russia-Ukraine conflict that erupted in 2014. The authors prove that Poland, Lithuania, Estonia and Latvia are united by perception that the Russian aggression in Ukraine is a threat to their national security, they support for tough policy of anti-Russian sanctions in the international arena, and assist Ukraine and the level of declarations and at the level of action. Nonetheless , level of their participation and support for Ukraine depends on their actual capabilities and domestic and foreign policy priorities. Reactions of other V4 countries to events in Ukraine are more restrained and vary from quiet pragmatism in Slovakia to clear pro-Russian voices in the Czech Republic and Hungary. It is unlikely, however, that their position can be a real obstacle to the implementation of the common EU action in the near future.